Investigating the potential of endophytic lactic acid bacteria isolated from papaya seeds as plant growth promoter and antifungal agent - Mohd Jaini, Mohammad Fahrulazri; Roslan, Nurfaten Farhanah; Yusof, Mohd Termizi; Saidi, Noor Baity; Ramli, Norhayati; Mohd Zainudin, Nur Ain Izzati; Mohd Hashim, Amalia (Universiti Putra Malaysia Press, 2022)
Endophytic lactic acid bacteria (LAB) isolated from papaya seeds, including a consortium of two LAB isolates, Weissella cibaria PPKSD19 and Lactococcus lactis subsp. lactis PPSSD39 could previously inhibit papaya dieback disease causative agent, Erwinia mallotivora BT-MARDI in vitro, indicating their potential as biofertilizer. However, further characterizations on other plant growth-promoting (PGP) properties of the LABs are prerequisite to use in agricultural settings as bio-inoculum. Hence, this study aimed to evaluate PGP potentials further and in vitro antifungal activity of the LABs against various plant pathogens. The LAB isolates were tested positive in indole-3-acetic acid (IAA), siderophore, and ammonia production and could solubilize phosphate. Weissella cibaria PPKSD19 and L. lactis subsp. lactis PPSSD39 exhibited the strongest in vitro antifungal activity against Fusarium oxysporum TKA and Curvularia lunata. Inoculum concentration of 1x10 cfu/ml of W. cibaria PPKSD19 and L. lactis subsp. lactis PPSSD39 mixture showed the highest increment in shoot and root dry weight. In conclusion, W. cibaria PPKSD19 and L. lactis subsp. lactis PPSSD39 consortium displayed promising plant probiotic potential. These results highlighted the possibility of the bacterial consortium to be exploited as bioinoculant to promote plant growth and inhibit phytopathogens causing plant diseases.